Parameters that influence the chromatic variation of porous face ceramic waterproofed with organosilicic products - Coronado Martín, Jesús Ángel; García Santos, Alfonso (Revista de la Construcción. Journal of Construction, 2017)
All water repellent products, theoretically colorless, when applied superficially in the porous face ceramic, produce a chromatic variation in the color of the ceramic. The factors that influence the color variation are explored. The ceramic is selected according to its type of manufacture: manual, pressed and extruded, characterizing it considering the absorption coefficient, open porosity, absorption rate, surface finishing and initial color parameters. The water repellent products are selected on the basis of their chemical composition. The final color of the waterproofing ceramics is analysed together with the parameters obtained from the characterization of the ceramic, noting that the only color variation depends on the initial color of the ceramic, existing a linear relationship between the initial and final color of the waterproofing ceramics with each of the products. The final color of a ceramic can be predicted, depending on the composition of the water repellent product being applied.